2011
DOI: 10.2196/jmir.1683
|View full text |Cite
|
Sign up to set email alerts
|

Do Family Physicians Retrieve Synopses of Clinical Research Previously Read as Email Alerts?

Abstract: BackgroundA synopsis of new clinical research highlights important aspects of one study in a brief structured format. When delivered as email alerts, synopses enable clinicians to become aware of new developments relevant for practice. Once read, a synopsis can become a known item of clinical information. In time-pressured situations, remembering a known item may facilitate information retrieval by the clinician. However, exactly how synopses first delivered as email alerts influence retrieval at some later ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The participants were 41 practicing family physicians (24 men and 17 women, 28 to 70 years old) from nine Canadian provinces, and their context of clinical practice was primary healthcare. This sample was opportunistically selected for studies of the impact of information on the family physician . The dissemination method was distribution of one research synopsis per weekday by e‐mail, over 49 weeks in 2008.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were 41 practicing family physicians (24 men and 17 women, 28 to 70 years old) from nine Canadian provinces, and their context of clinical practice was primary healthcare. This sample was opportunistically selected for studies of the impact of information on the family physician . The dissemination method was distribution of one research synopsis per weekday by e‐mail, over 49 weeks in 2008.…”
Section: Methodsmentioning
confidence: 99%
“…This sample was opportunistically selected for studies of the impact of information on the family physician. 28 The dissemination method was distribution of one research synopsis per weekday by email, over 49 weeks in 2008. The method to capture assessments was the Information Assessment Method (IAM) 29,30 that links a validated questionnaire to each information object.…”
Section: Methodsmentioning
confidence: 99%
“…The IAM can help assess electronic knowledge resources in the context of the “pull” or the “push” of information. A “push-pull acquisition-cognition-application” of information conceptual framework has been published elsewhere [ 2 , 14 ]. On the one hand, “pull” refers to information-seeking behavior, such as a search for information in an electronic knowledge resource.…”
Section: Introductionmentioning
confidence: 99%
“…The sixth study examined self-reported cognitive impact of emailed synopses of recently published clinical research, and indicated that email alerts have a positive impact [ 19 ]. Subsequently, another study indicated that email alerts are infrequently retrieved after initial reading [ 20 ]. Finally, two studies suggested that email dissemination of synopses of systematic literature reviews [ 21 ], and of treatment recommendations is associated with anticipated benefits for patient health [ 3 ].…”
Section: Introductionmentioning
confidence: 99%